The Effect of Calcium Alginate Primary Dressing on Diabetic Ulcer Healing in Proliferative Phase - Husni; Septiyanti; Idramsyah; Mardiani; Rahma Annisa; Bella Samya Dwi Putri (Window of Health : Jurnal Kesehatan, 2026)
Diabetes Mellitus (DM) is a global health issue, with diabetic ulcers being a common complication and a high mortality rate. In 2021, around 576 million people worldwide had DM, and this number is projected to reach 643 million by 2030 and 787 million by 2045. The healing process of these ulcers is accelerated in a moist environment and with the use of appropriate primary dressings, such as Calcium Alginate. Objective: The aim is to determine the effect of Calcium Alginate primary dressing on the acceleration of diabetic ulcer healing during the proliferative phase. Methods: This research uses a quantitative study design with a quasi-experimental approach with a control group, employing a pre-test and post-test design. Respondents were divided into two groups: the intervention group and the control group. The intervention group received treatment with calcium alginate, while the control group received treatment with zinc cream. The sample was selected using the consecutive sampling technique. Results: The results of the research indicate a significant difference in the average rate of diabetic ulcer healing between the intervention and control groups. Conclusions: The statistical test was performed using an independent sample T-Test, resulting in a p-value of 0.000 (p ≤ α 0.05), indicating a significant effect of the Calcium Alginate primary dressing on the acceleration of diabetic ulcer healing during the proliferative phase, thus supporting its use in enhancing the healing process of diabetic ulcers in this phase.